Algebraic Interpolating Polynomials of Theobromine Using Numerical Techniques - G. , Srinivasa; P., K. Asha (International Journal of Psychosocial Rehabilitation, 2020)
Here, applying the known numerical techniques, algebraic interpolating polynomials are derived for theobromine, which is oxidized by potassium permanganate in an alkaline medium. The kinetics was measured using a UV-visible spectrophotometer. The ionic strength was maintained at 0.05 mol/dm³. For the study, it was observed to be a 1st-order reaction with respect to the concentration of substrate and oxidant. A complex formed in the intermediate step decomposes slowly to form free radicals. The free radicals that are generated react further to form the final product, which is identified by spot test and spectral studies.